Genetic control of immune-mediated necrosis of Mycobacterium avium granulomas - Flórido, Manuela (Blackwell Science Inc, 2006)
Intravenous infection of C57BL/6 and C57BL/10 mice with low doses of a highly virulent strain of Mycobacterium avium (ATCC 25291) led to the development of granulomas that underwent necrosis. In contrast, neither BALB/c nor DBA/1 mice developed granuloma necrosis after such infection despite a similar course of mycobacterial proliferation. Studies with C57BL/10 mice congenic for the Hc locus revealed that an intact complement C5 gene is required for granuloma necrosis. On the other hand, genetic disruption of the interleukin-10 gene in BALB/c mice made this strain susceptible to granuloma necrosis.